Analisis Penyebab Tunggakan Pembayaran Rekening Air Pelanggan pada Perusahaan Daerah Air Minum (PDAM) Tirta Sari Binjai - Mutiara, Mutiara; Siregar, Saparuddin (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
PDAM Tirta Sari Binjai is a company engaged in the provision and service of clean water for the people of Binjai and its surroundings. PDAM Tirta Sari Binjai's operations finance itself from PDAM Tirta Sari's revenue for customers who use PDAM Tirta Sari's services. However, the revenue received by PDAM Tirta Sari is not optimal due to the high level of customer arrears at PDAM Tirta Sari Binjai. The purpose of this study is to find out what factors can cause arrears in customer water payments at the Tirta Sari Binjai Regional Drinking Water Company (PDAM). This study uses a descriptive method with a qualitative approach. This research was also conducted through interviews/interviews, observation and analysis of documents when conducting research. The results showed that the factors that led to arrears were: 1) The customer's water meter was buried, 2) The door or fence of the customer's house was locked, 3) The customer's water was small or completely turned off, 4) Notification of arrears was not delivered by the officer, 5 ) The habit of customers to delay payments, 6) Lack of officers to make terminations, 7) Per capita income of customers has decreased due to the covid-19 pandemic.